Lessons in mortality doctors and patients struggling together - Weisse, Allen B. (University of Missouri Press, 2006)
"Writing frankly, Weisse discusses how doctors and patients of cancer, heart disease, stroke, infectious disease, AIDS, and other dire diagnoses deal with illness in the twenty-first century, considering, in turn, how such factors as specialization, rising costs, managed care, the insurance industry, and litigation has changed the practice of medicine"--Provided by publisher.